PERANAN BUSINESS DEVELOPMENT SERVICE DALAM PENGEMBANGAN USAHA KECIL MENENGAH SETELAH MASA PANDEMIC COVID-19 DI KOTA WISATA PARIAMAN (STUDI KASUS UKM PRODUK KREATIF) - Arivetullatif Arivetullatif; Sulastri Sulastri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research was conducted through hypothesis testing using multiple regression analysis. The population in this study were all beautiful embroidery and embroidery craftsmen in the tourist city of Pariaman (case study of creative products), with a population of 1,117 business units. The sampling technique used is purposive sampling, where the researcher uses considerations by including certain elements that are considered to be able to obtain correct information or the individuals in the sample that reflect the population. Based on the theory above, in taking the sample, the researcher used a sample of 20% of the population, namely 20% x 1117 = 223.4 :2 = 111.7 so that it was rounded up to 112 entrepreneurs as respondents. Multiple regression results Y = 0.00 + 0.044 X1 + 0.00 X2 + 0.00X3 In the multiple linear regression equation, it is known that the constant is -7.073. Business Development Service in facilitating Small and Medium Enterprises to obtain capital and expand market share is a variable that has a significant role in the development of Small and Medium Enterprises, meaning that Business Development Service in facilitating Small and Medium Enterprises to obtain capital and expand market share has a significant role in business development Small and Medium has a beautiful and border crossing in Pariaman city tourism. While the Business Development Service in facilitating Small and Medium Enterprises to master technology is statistically significant, it means that the role of Business Development Service in facilitating Small and Medium Enterprises to master technology in developing Small and Medium Enterprises with beautiful embroidery and embroidery needs to be done significantly. This shows that the first and second hypotheses are proven and can be accepted as true as well as the third hypothesis is proven to be true. Simultaneously Business Development Service has a role. significant in the development of Small and Medium Enterprises Beautiful embroidery and embroidery in Pariaman city.Keywords: Small and Medium Enterprise(UKM), Business Development Service (BDS).